Risk of immunotherapy-related narcolepsy in genetically predisposed patients: a case report of narcolepsy after administration of pembrolizumab - Shigehira Saji; Emi Tokuda; Takashi Kanbayashi; Yutaka Natori; Eisaku Sasaki; Shu Soeda; Shigenori Furukawa; Yusuke Azami (Journal for ImmunoTherapy of Cancer)
Background Immune-related adverse events associated with immune checkpoint therapy cause autoimmune disease-like symptoms. People who carry specific genotypes or haplotypes of human leucocyte antigen (HLA) are known to be predisposed to develop autoimmune diseases including narcolepsy. Immunotherapy could be a trigger to develop narcolepsy in predisposing HLA positive patients.Case presentation A 66-year-old woman with stage IVB endometrial carcinosarcoma experienced daytime sleepiness and temporary muscle weakness 14 days after the administration of an immune checkpoint inhibitor, pembrolizumab. These were consistent with the main symptoms of narcolepsy with cataplexy. This patient carried a highly predisposing HLA haplotype for narcolepsy; HLA-DQB1*06:02, DRB1*15:01, DQA1*01:02 and DRB5*01:01:01. A hypocretin-1/orexin-A concentration in the patient’s cerebrospinal fluid was low at 9.6 pg/mL in ELISA, and 155.5 pg/mL in radioimmunoassay that was below the normal level of 200 pg/mL. Therefore, she was diagnosed with narcolepsy tentatively according to the International Classification of Sleep Disorders, third edition diagnostic criteria for narcolepsy. The onset of narcolepsy in the 60s is very rare, and narcoleptic symptoms in our patient were likely to be caused by pembrolizumab.Conclusions This case suggests that treatment with immune checkpoint inhibitors potentially causes narcolepsy in genetically predisposed patients.